Analog experiments for the identification of trace biosignatures in ice grains from extraterrestrial ocean worlds - Klenner, Fabian; Postberg, Frank; Hillier, Jon; Khawaja, Nozair A.; Reviol, René; Stolz, Ferdinand; Cable, Morgan L.; Abel, Bernd; Nölle, Lenz (Astrobiology, 2020)
Reliable identification of biosignatures, such as amino acids, fatty acids, and peptides, on extraterrestrial ocean worlds is a key prerequisite for space missions that search for life or its emergence on these worlds. One promising approach is the use of high-performance in situ impact ionization mass spectrometers to sample water ice grains emerging from ocean-bearing moons such as Europa or Enceladus. A predecessor of such detectors, the Cosmic Dust Analyzer on board the Cassini spacecraft, has proven to be very successful in analyzing inorganic and organic ocean constituents and with that characterizing the habitability of Enceladus ocean. However, biosignatures have not been definitively identified in extraterrestrial ocean environments so far. Here, we investigate with an analog experiment the spectral appearance of amino acids, fatty acids, and peptides in water ice grains, together with their detection limits, as applicable to spaceborne mass spectrometers. We employ a laboratory-based laser induced liquid beam ion desorption technique, proven to simulate accurately the impact ionization mass spectra of water ice grains over a wide range of impact speeds. The investigated organics produce characteristic mass spectra, with molecular peaks as well as clearly identifiable, distinctive fragments. We find the detection limits of these key biosignatures to be at the μM or nM level, depending on the molecular species and instrument polarity, and infer that impact ionization mass spectrometers are most sensitive to the molecular peaks of these biosignatures at encounter velocities of 4-6 km/s.
Online ahead of print: December 11, 2019
Gesehen am 11.03.2020